Is There a Single Method for the Internet of Things? - JACOBSON, IVAR; SPENCE, IAN; PAN-WEI NG (Communications of the ACM, 2017)
The article discusses the significance of the Internet of Things (IoT) in technological development and argues that the computer software industry will require several methods for problem solving as the IoT develops and expands. It focuses on the Ignite IoT Methodology and the IoT Methodology, the need for new practices, and the concept of essence.